Binding of pulmonary surfactant proteins A and D to Aspergillus fumigatus conidia enhances phagocytosis and killing by human neutrophils and alveolar macrophages. - Madan, T (1997)
To determine whether the lung surfactant proteins A (SP-A) and D (SP-D) are involved in the initial protective immunity against opportunistic pulmonary fungal infections caused by Aspergillus fumigatus, we performed a series of in vitro functional studies to see if SP-A and SP-D enhanced binding, phagocytosis, activation, and killing of A. fumigatus conidia by human alveolar macrophages and circulating neutrophils. Both SP-A and SP-D bound to carbohydrate structures on A. fumigatus conidia in a calcium-dependent manner. SP-A and SP-D were also chemoattractant and significantly enhanced agglutination and binding of conidia to alveolar macrophages and neutrophils. Furthermore, in the presence of SP-A and SP-D, the phagocytosis, oxidative burst, and killing of A. fumigatus conidia by neutrophils were significantly increased. These findings indicate that SP-A and SP-D may have an important immunological role in the early antifungal defense responses in the lung, through inhibiting infectivity of conidia by agglutination and by enhancing uptake and killing of A. fumigatus by phagocytic cells.